Learning Medium Promoting English Productive Skills through Instagram in Universitas Nahdlatul Ulama Lampung: English - ruri supatmi ruri; purna wiratno purna; Fajrianor (Prodi Tadris Bahasa Inggris, 2024)
Digital generation is influenced by developing technology. Digital generation is called the children who were born in 1995 to 2010. The internet has transformed their life. They have been grown in a world of instant access to knowledge and information, a world automation, remote controls, and stimulation abilities to stimulate the mind. They usually use Instagram to share their personal information, such as uploading their pictures or videos and providing an explanation that is called caption under it. Thus, this study intended to know the students’ perception of using Instagram to improve their productive skills. Teaching English through social media like Instagram is one of the best solutions for lecturers to avoid traditional class This study was conducted on the students of Universitas Nahdlatul Ulama Lampung. The method of this study was a descriptive qualitative study. The researcher uses 36 students and two lecturers. This study uses questionnaire, interview, observation and documentation. This uses hidden identity to protect their privacy. the researcher also was being hidde observer. The researcher uses miles and Huberman to identify the data.The result of this study showed Instagram is one of the applications that used by digital generation to learn English specially the students of Universitas Nahdlatul Ulama Lampung perceived that Instagram helped them to improve their productive skills especially in English Learning such as writing and speaking abilities. They can learn every time and everywhere. All they life is on social media. Instagram can be used for positive things for the students.